Quality of Life among Postnatal Mothers attending Immunization Clinic of a Tertiary Level Hospital - Budhathoki, Roshina; Ghimire, Binda (Journal of Karnali Academy of Health Sciences, 2022)
Background: Postnatal period is a transition period marked by physical, emotional and relationship changes. Yet, the most neglected period than before and during childbirth as stated by World Health organization (WHO). Quality of Life (QOL) is an individual’s perception of their position in life in relation to their goals and expectations that indicates unmet needs and intervention outcomes. Demands made by childbirth on mother’s wellbeing can lead to poor QOL in postnatal period. Thus, the objective of the study was to identify QOL among postnatal mothers. Method: Descriptive cross-sectional research design was used to find QOL. 217 postnatal mothers were selected using convenience sampling technique. Data was collected using structured interview schedule containing WHOQOL-BREF questionnaires. Data analysis was done using descriptive statistics i.e. frequency, percentage, mean and standard deviation to summarize data and inferential statistics i.e. independent t-test and one way ANOVA to compare domain scores with selected variables. Result: The highest mean score was on social relationship domain (70.06 ± 14.62) denoting highest QOL in this domain, followed by psychological (68.36 ± 17.90), Physical (67.08 ± 24.79) and environment domain (64.38 ± 16.59) respectively. Significant difference was found between domain scores and age, education, pregnancy type, ANC visit, delivery type, perineal trauma (p<0.05). Conclusion: QOL of postnatal mother tend to get affected by socio-demographic and obstetric factors. Improving quality and continuity of care from antenatal to postnatal period will help to improve QOL among postpartum mothers.